2011
DOI: 10.48550/arxiv.1107.0689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancement of the Superconducting Transition Temperature under Pressure in Rare-Earth Doped Ca$_{1-x}$La$_x$Fe$_2$As$_2$ (x=0.27)

Abstract: We report measurements of the pressure dependence of the superconducting transition temperature Tc in single crystal samples of the rare-earth doped superconductor Ca0.73La0.27Fe2As2. We track Tc with two techniques, via in-plane resistivity measurements and with a resonant tunnel diode oscillator circuit which is sensitive to the skin depth. We show that initially Tc rises steeply with pressure, forming a superconducting dome with a maximum Tc of ∼ 44 K at 20 kbar. We discuss this observation in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…23) in CaFe 2 As 2 mainly due to close matching between ionic-radii of RE and Ca, and that their incorporation suppresses the low temperature AFM ordering in favor of the superconducting phase. Application of hydrostatic pressure on the doped materials is shown to increase further the critical temperature 25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23) in CaFe 2 As 2 mainly due to close matching between ionic-radii of RE and Ca, and that their incorporation suppresses the low temperature AFM ordering in favor of the superconducting phase. Application of hydrostatic pressure on the doped materials is shown to increase further the critical temperature 25 .…”
mentioning
confidence: 99%
“…This subject was revived with the discovery of high temperature superconductivity (up to 45-49 K) in CaFe 2 As 2 doped with trivalent rare-earth (RE) metal atoms (La, Pr, Ce, Nd) substituting the divalent Ca atoms [21][22][23][24][25] . It was demonstrated that rare earths have high solubility (up to 27% in Ref.…”
mentioning
confidence: 99%
“…Theoretical calculations show clear differences between hole-and electron-doped systems [7] and predict that superconductivity can sustain higher hole than electron doping [8]. Despite of this fact it was found recently that the superconducting transition temperature T c reaches 45 K (under pressure) in the case of La 3+ for Ca 2+ substitution [9][10][11], and as high as 49 K for Pr 3+ indirect doping, as shown by resistive, magnetic and thermoelectric measurements [12]. It is unclear, however, whether the superconducting transition observed is bulk [9] or non-bulk [12] due to interfacial or filamentary superconductivity.…”
mentioning
confidence: 99%